The impact of employees' pro-environmental behaviors on corporate green innovation performance: The mediating effect of green organizational identity - Cheng, Zujie; Wu, Banggang; Deng, Xiaoyu; Li, Wei (Frontiers in Psychology, 2022)
Corporate green innovation performance becomes an important issue for nowadays companies with the increasing seriously global environmental condition. However, research that investigates pro-environmental behaviors from the employee’s perspective remains scarce, especially in emerging markets, which would limit the sustainable development of a company. This study develops an original framework of green organizational identity to explore the effects of employees’ pro-environmental behaviors on corporate green innovation performance and the underlying mechanism by conducting a survey in China. The results of the empirical analysis show that employees’ pro-environmental behaviors increase the corporate green innovation performance by positively influencing the green organizational identity. In addition, this paper also unveils that the leader’s pro-environmental behaviors positively influence the green innovation performance. Meanwhile, the innovation resistance (both technology and resource) shows a negative effect on the green innovation performance. This paper contributes to theoretical research and practical decision in the green organizational behavior area.